The Role of Rho GTPases in Motility and Invasion of Glioblastoma Cells - Houssam Al-Koussa; Oula El Atat; Leila Jaafar; Hagop Tashjian; Mirvat El-Sibai (Analytical Cellular Pathology)
Astrocytomas are primary malignant brain tumors that originate from astrocytes. Grade IV astrocytoma or glioblastoma is a highly invasive tumor that occur within the brain parenchyma. The Rho family of small GTPases, which includes Rac1, Cdc42, and RhoA, is an important family whose members are key regulators of the invasion and migration of glioblastoma cells. In this review, we describe the role played by the Rho family of GTPases in the regulation of the invasion and migration of glioblastoma cells. Specifically, we focus on the role played by RhoA, Rac1, RhoG, and Cdc42 in cell migration through rearrangement of actin cytoskeleton, cell adhesion, and invasion. Finally, we highlight the importance of potentially targeting Rho GTPases in the treatment of glioblastoma.